Thraustochytrids from Mangrove Leaves at Mangrove Resources Development Station 2 Tha Son, Chanthaburi Province - อุ่ยยก อุทุมพร; สวนจิตร สุดารัตน์; จริตควร สมถวิล (Princess of Naradhiwas University Journal, 2019)
Diversity of thraustochytrids from fallen senescent leaves of 11 mangrove trees collected from Mangrove Resources Development Station 2 Tha Son, Chanthaburi Province were investigated. A total of 123 isolates of thraustochytrids were found which classified into 3 species, namely Aurantiochytrium mangrovei, Aurantiochytrium limacinum and Aurantiochytrium sp. The frequency of occurrence of these thraustochytrids were 5 – 40 % and A. mangrovei was the predominant species. This study also found 21 isolates (1 species)of Aplanochytrids (Aplanochytrium sp.) which is close to a group of thraustochytrids and expressed as 5 – 35 % of occurrence. Consider with the species of mangrove trees, the percentage of occurrence were rather high in leaves of Avicennia alba, Acrostichum aureum and Xylocarpus moluccensis. The highest biomass was found in Aurantiochytrium sp. BUCHA0101 (18.01 ± 3.36 g/L), whereas A. limacinum, A. mangrovei, and Aplanochytrium sp. were quit similar amount (15.35 - 16.77 g/L). For fatty acid content analyzed by Gas Chromatography 6890, docosahexaenoic acid (DHA) was found in a range of 138.82 - 182.08 mg/g dry wt. (29.69 – 34.99 % of total fatty acids), while docosapentaenoic acid and arachidonic acid were found of 28.99 – 43.63 mg/g dry wt. (6.57 – 8.38 % of total fatty acids) and of 0.38 – 0.46 mg/g dry wt. (0.08 – 0.10 % of total fatty acids), respectively.